STRATEGI GURU PENDIDIKAN AGAMA ISLAM DALAM PENANGANAN PERILAKU RESISTENSI SISWA DI MADRASAH IBTIDAIYAH - Muhammad Kadrida; Ramlan Thalib; Khairul Washfiah (Ahsani Taqwim: Jurnal Pendidikan dan Keguruan, 2025)
Education plays an important role in addressing resistance, especially in the form of student resistance behavior in madrasahs, which is one of the problems often faced by teachers, such as rejection, protests, or even violence against teachers or classmates. This research aims to identify the strategies implemented by Islamic Religious Education teachers in addressing student resistance. The subjects of this research are four Islamic Education teachers, while the object of the research is the strategies used by Islamic Education teachers to address students’ resistance behavior. The data collection technique for this research uses a qualitative approach that is descriptive in nature. With data collection techniques used through observation, interviews, and documentation. The data processing techniques used are data collection, data reduction, data display, data verification, and data analysis. And the verification of the data validity used in this research includes data credibility, transferability, dependability, and confirmability. The research results show that the teacher's strategy in handling resistance in learning is quite good. This was known from the results of the interview with the teacher. Then, in addressing student resistance, there were some obstacles such as not wanting to follow the teacher’s advice. The factor causing the handling of resistance is found in the madrasa activities, which can foster religiosity and socialization among peers, ultimately aimed at the students’ character. Therefore, the teacher periodically changes strategies by observing the students’ conditions, and there are also hindering factors such as students feeling afraid and not liking the teaching style presented by the teacher.